Evaluation of Effectiveness of Local Delivery Simvastatin Gel 1% as an Adjunctive Treatment to Non-surgical Therapy in Periodontitis (stage 2, grade B) - الخليف, مضر; يوسف, تهامة; الهوشي, لمى (Latakia University Journal -Medical Sciences Series, 2023)
Non-surgical periodontal treatment is considered the corner stone in treatment of periodontitis, it includes mechanical treatment supported by adjunctive use of systematic and local drugs, this drugs in all their diversity improved clinical outcomes of mechanical treatment. simvastatin is a drug helps in osteoconduction with its anti-inflammatory properties, therefore it improves periodontal tissues statues. Aim of the study is to Evaluate the efficacy of 1% simvastatin gel as an adjunctive treatment for non-surgical treatment in patients with periodontitis (stage 2, grade B). The study sample included 20 (upper or lower) jaws of patients with periodontitis (stage 2, grade B), after mechanical treatment simvastatin gel was applied in one quadrant of the jaw (test group), and mechanical treatment in the other quadrant of the same jaw (control group). With the study of Gingival index (GI) and clinical attachment level (CAL) before treatment and 3-6 months after treatment. there were statistically significant differences between the two groups in GI and CAL indices after 3-6 months, and the improvement was greater in the study group. this study shows that simvastatin can improve GI and CAL indices in patients with periodontitis (stage 2, grade B), with the ability of preparing it simply and cost effectively.